2021
DOI: 10.1101/2021.06.15.447407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual dimorphism in a neuronal mechanism of spinal hyperexcitability across rodent and human models of pathological pain

Abstract: The prevalence and severity of many chronic pain syndromes differ across sex, and recent studies have identified differences in immune signalling within spinal nociceptive circuits as a potential mediator. Although it has been proposed that sex-specific pain mechanisms converge once they reach neurons within the superficial dorsal horn (SDH), direct investigations using rodent and human preclinical pain models have been lacking. Here, we discovered that in the Freund′s Adjuvant in vivo model of inflammatory pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Because BDNF is not necessary for the development of allodynia in female rodents ( 27 ), the mediator released from adaptive immune cells remains to be determined. Similar findings have been found in the Freund's adjuvant in vivo model of inflammatory pain in rodents and confirmed in human neurons ( 33 ). These authors also showed that ex vivo BDNF enhanced synaptic NMDA receptor responses in lamina I neurons from males but not from females and that ovariectomy eliminated these differences.…”
Section: General Comments Regarding Injury-induced Signaling In the S...supporting
confidence: 87%
See 3 more Smart Citations
“…Because BDNF is not necessary for the development of allodynia in female rodents ( 27 ), the mediator released from adaptive immune cells remains to be determined. Similar findings have been found in the Freund's adjuvant in vivo model of inflammatory pain in rodents and confirmed in human neurons ( 33 ). These authors also showed that ex vivo BDNF enhanced synaptic NMDA receptor responses in lamina I neurons from males but not from females and that ovariectomy eliminated these differences.…”
Section: General Comments Regarding Injury-induced Signaling In the S...supporting
confidence: 87%
“…Neuropathic pain is seen more frequently in women than in men ( 29 ) and it is now recognized that understanding of divergent pain mechanisms in males vs. females is crucial to the development of appropriate therapeutic approaches ( 28 , 33 , 450 , 451 ).…”
Section: General Comments Regarding Injury-induced Signaling In the S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophage invasion of DRG is predominant in males and not in females ( 453 ) and nociception is regulated by spinal serotonin and noradrenaline in male but not in female mice ( 454 ). It has also recently been shown that ex vivo treatment of live human organ donor spinal cord tissue with BDNF downregulates markers of inhibition and upregulates markers of facilitated excitation in dorsal horn neurons from males but not females ( 455 ). Lastly, administration of IL-23 (Interleukin 23) produces mechanical allodynia in female but not male mice and chemotherapy-induced mechanical pain is selectively impaired in female mice lacking IL-23 or its cognate receptor.…”
Section: Discussionmentioning
confidence: 99%